2007
DOI: 10.1016/j.trstmh.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Antischistosomal efficacy of artesunate combination therapies administered as curative treatments for malaria attacks

Abstract: Artesunate is a highly effective anti-malarial and there is some evidence that it is also active against schistosome infections. Therefore, we investigated whether treatment with artesunate of acute malaria in Senegalese children had an impact on their level of infection with Schistosoma haematobium. Twenty seven children entered into a clinical trial of antimalaria treatment were excreting eggs of S. haematobium in their urine on the day of treatment, 15 of whom received the combination of a single dose of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 12 publications
2
40
0
1
Order By: Relevance
“…artesunate, amodiaquine and sulphadoxine-pyremethamine were also reasonably effective (Thiong'o et al, 2002;Inyang-Etoh, 2004;Boulanger et al, 2007;Inyang-Etoh et al, 2009). Oxamniquine is the only main alternative antischistosomal drug, but its use is declining and moreover in contrast to praziquantel, which displays activity against all human schistosome species, the activity of oxamniquine is confined to S. mansoni (Utzinger et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…artesunate, amodiaquine and sulphadoxine-pyremethamine were also reasonably effective (Thiong'o et al, 2002;Inyang-Etoh, 2004;Boulanger et al, 2007;Inyang-Etoh et al, 2009). Oxamniquine is the only main alternative antischistosomal drug, but its use is declining and moreover in contrast to praziquantel, which displays activity against all human schistosome species, the activity of oxamniquine is confined to S. mansoni (Utzinger et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The antimalarial drugs particularly the derivatives of artemisinin (e.g., artemether and artesunate), have been shown to be schistosomicidal and have exhibited high parasitological cure rates. Consequently discussions are on-going on how this evidence base can be translated into sound public health actions and the possible implications especially in sub-Saharan Africa where the malaria scourge is most severe (Utzinger et al, 2001a;2001b;Inyang-Etoh et al, 2009;Boulanger et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although monotherapy with artesunate (ART) in Schistosoma haematobium-infected children yields a low cure rate of 21% (Keiser et al 2010), a high cure rate of 100% was obtained with the combination therapy of ART and AQ (Boulanger et al 2007). These results suggest that AQ strongly exhibits antischistosomal activity.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that artemether was active against S haematobium (N'Goran et al, 2003). Boulanger et al (2007) have also associated artesunate combination therapies with high cure rate of S. haematobium infection in Senegal. This author and colleagues investigated the efficacy of artesunate in the treatment of urinary schistosomiasis in Nigeria (Inyang-Etoh et al, 2004) (Table 2).…”
Section: Efficacy Of Artemisinin In Field Studiesmentioning
confidence: 99%